LncRNA MALAT1 targeting miR‐124‐3p regulates DAPK1 expression contributes to cell apoptosis in Parkinson's Disease. Issue 12 (10th April 2020) - Lu, Yi; Gong, Zhongying; Jin, Xiaojie; Zhao, Peng; Zhang, Yuting; Wang, Zhiyun
Abstract: Death associated protein kinase 1 (DAPK1) was initially discovered in the progress of gamma‐interferon induced programmed cell death, it is a key factor in the central nervous system, including Parkinson's disease (PD). However, the underlying mechanisms of DAPK1 in PD remain unclear and this research work aims to explore the potential mechanisms of DAPK1 in PD. In the study, we exposed SH‐SY5Y cells to MPP + and treated mice with MPTP to investigate the roles of DAPK1 in PD and the underlying mechanisms. The results indicated that the expression of DAPK1 is significantly upregulated and negatively correlated with miR‐124‐3p levels in SH‐SY5Y cells treated by MPP +, and miR‐124‐3p mimics could effectively inhibit DAPK1 expressions and alleviate MPP + ‐induced cell apoptosis. In addition, knockdown MALAT1 reduces the levels of DAPK1 and the ratio of SH‐SY5Y cell apoptosis, which is reversed via miR‐124‐3p inhibitor in vitro. Similarly, knockdown MALAT1 could improve behavioral changes and reduce apoptosis by miR‐124‐3p upregulation and DAPK1 downregulation in MPTP induced PD mice. Taken together, our data showed that lncRNA MALAT1 positively regulates DAPK1 expression by targeting miR‐124‐3p, and mediates cell apoptosis and motor disorders in PD. In summary, these results suggest that MALAT1/miR‐124‐3p /DAPK1 signaling cascade mediates cell apoptosis in vitro and in vivo, which may provide experimental evidence of developing potential therapeutic strategies for PD. Abstract : Our data showed that long nocoding RNA MALAT1 positively regulates death‐associated protein kinase 1 expression by targeting miR‐124‐3p and mediates cell apoptosis and motor disorders in Parkinson's disease (PD). These results provided experimental evidence of developing potential therapeutic strategies for PD.